Validation of the Multidimensional Inventory for Religious Spiritual Well-being with Iranian samples. Issue 6 (3rd July 2019) - Dadfar, Mahboubeh; Lester, David; Turan, Yahya; Beshai, James A.; Unterrainer, Human-Friedrich
ABSTRACT: This study was designed to investigate the validation of a Farsi version of the Multidimensional Inventory for Religious Spiritual Well-being (MI RSWB 48) in a convenience sample of 442 Iranian people. Respondents completed a series of demographic questions and the MI RSWB 48. The Cronbach's α coefficient was .82. The MI RSWB 48 items identified two factors, but these factors did not match the two dimensions for which the scale was devised. The Hope Immanent (HI), and Experiences of Sense and Meaning (SM) subscales loaded on Factor 1, but General Religiosity (GR) was loaded on this factor rather than Forgiveness (FO). The Factor 2 had loadings from the FO and Hope Transcendent (HT) subscales. Furthermore, the FO subscale scores had weak associations with the scores for Transcendent dimension. This study suggests that the subscale scores on the MI RSWB 48 may have different implications for Christian and Muslim respondents.